Global Governance, COVID 19 & Resesi di Negara ASEAN - Tedy Chandra; Stefanny Valencia Halim; Fikri Fadilah (Proyeksi: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2022)
This paper aims to explain how the alleviation of the recession that "almost" occurred in the Southeast Asia region was caused by the COVID-19 pandemic in late 2019 and spread to the Southeast Asian region in 2020 through Global Governance. This is because the existence of problems regarding health has implications for other problems such as economic problems where economic conditions have decreased and almost caused a recession in several Southeast Asian countries. Global Governance seeks to control this problem by issuing an international regime in order to overcome the recession problem through library research methods such as books, journals, articles and trusted website pages in searching for data and information about the writing that is done.